2016
DOI: 10.1016/j.socscimed.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and drinking: A systematic review of the evidence

Abstract: Although it is widely accepted that discrimination is associated with heavy and hazardous drinking, particularly within stress and coping frameworks, there has been no comprehensive review of the evidence. In response, we conducted a systematic review of the English language peer-reviewed literature to summarize studies of discrimination and alcohol-related outcomes, broadly defined. Searching six online data bases, we identified 937 non-duplicative titles published between 1980 and 2015, of which 97 met all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
146
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 126 publications
11
146
3
1
Order By: Relevance
“…Others suggest that some immigrant groups possess protective characteristics such as family cohesion that may be lost in future generations of the U.S.-born (Marsiglia et al, 2009b; Rivera et al, 2008; Canino et al, 2008; Estrada-Martinez, et al, 2011). Some have suggested that the poorer health indices of subsequent U.S.-born members of immigrant groups are due to the frustration associated with difficulty in fulfilling ambitions of socioeconomic betterment due to segregation and discrimination, all factors of risk for increased involvement with substance use (Smedley et al, 2003; Mason et al, 2011; Cooper et al, 2007; Williams and Collins, 2001; Landrine and Klonoff, 2000; Gilbert and Zemore, 2016; Brondolo et al, 2009; Tran et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others suggest that some immigrant groups possess protective characteristics such as family cohesion that may be lost in future generations of the U.S.-born (Marsiglia et al, 2009b; Rivera et al, 2008; Canino et al, 2008; Estrada-Martinez, et al, 2011). Some have suggested that the poorer health indices of subsequent U.S.-born members of immigrant groups are due to the frustration associated with difficulty in fulfilling ambitions of socioeconomic betterment due to segregation and discrimination, all factors of risk for increased involvement with substance use (Smedley et al, 2003; Mason et al, 2011; Cooper et al, 2007; Williams and Collins, 2001; Landrine and Klonoff, 2000; Gilbert and Zemore, 2016; Brondolo et al, 2009; Tran et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Research findings have generally demonstrated a positive association between experiences of racial/ethnic discrimination, drinking and alcohol-related consequences among minorities (Martin et al, 2003, Gee et al, 2007; Mulia et al, 2008, Chae et al, 2008, Mulia et al, 2009; Tran et al, 2010; Borrell et al, 2010; Zemore el al., 2011; Mulia and Zemore, 2012; Borrell et al, 2013; Otiniano Verissimo et al, 2014; Zemore et al, 2016; Gilbert and Zemore, 2016). For example, Martin et al (2003) found that among a national sample of Blacks, reports of discrimination more than doubled the odds of problem drinking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,22 Perceived discrimination increases risk of depression, 23 anxiety, 24 suicide, 25 and substance use. [26][27][28] Implicit bias also influences Blacks' opportunity for employment, education, and health care. [29][30][31][32] There is growing evidence suggesting that exposure and vulnerability to racial bias is a function of the intersection of race and gender, with Black men having higher exposure and vulnerability to discrimination than Black women.…”
Section: Introductionmentioning
confidence: 99%
“…However, while substance use is a well-established dysfunctional coping behavior for acute and chronic stressors [19–23], little is known about the relationship between gender discrimination and illicit substance use or substance use disorders among U.S. women. A recent review of the literature on discrimination and alcohol use found that of the 97 studies reviewed from the previous 35 years, only 3% focused on gender discrimination (compared 70% on racial/ethnic discrimination and 16% on sexual orientation discrimination) [24]. Studies in local or convenience samples of women show that gender discrimination is associated with substance use or abuse in college students [13], young adults [25], and those seeking family planning services [26].…”
Section: Introductionmentioning
confidence: 99%